The relationship of pre-racing food restrictions and gastrointestinal symptoms in master athletes - Saraç, Osman Emir; Eskici, Günay (VIREF Revista de Educación Física, 2024)
Objective: to evaluate the relationship between food restriction and gastrointestinal symptoms in master athletes. Method: totally, 246 master athletes (185 men, 61 women) who participated in training and racing at 5, 6-10 and 11-21km, marathon, and ultra-marathon took part in this research. To determine the relationship between food restrictions and gastrointestinal symptoms of master athletes, this research drew on the Food Restriction in Running Questionnaire which was developed by Parnell et al. (2019). The Fisher’s exact test determined significant differences between groups (gender, race distance, performance level) in the percent of master athletes who avoided pre-racing foods and experienced gastrointestinal symptoms. In all statistical analyzes, the level of statistical significance was set at p<0,05. Results: the most restricted foods pre-racing included high-fat foods (79%), junk foods (63%), spicy foods (58%), milk (54%) and red meat (44%). This study concluded that the most common gastrointestinal symptoms experienced during racing were gas (51%), stomach pain/cramp (43%), intestinal problems (pain) (42%), reflux/heartburn (39%) and nausea/vomiting (39%). On the gastrointestinal symptoms by gender, significant differences were found in constipation, gas, fullness/heaviness and burping, which were more commonly observed in the female athletes (p<0,05). This study also revealed that intestinal problems (pain) and gas increased with race distance and performance level (p<0,05). Conclusion: increasing the race distance and performance level increased the food restriction rates and incidence of gastrointestinal symptoms in master athletes. Furthermore, food restriction and the incidence of gastrointestinal symptoms were observed more in the female athletes.